Study on Relationship of Serum Total Cholesterol Low Density Lipoprotein and Triglycerides With Body Mass Index (Journal of Chittagong Medical College Teachers' Association, 2013)
The present case control study was designed to determined the relationship between serum Total cholesterol, Low Density Lipoprotein (LDL), Triglycerides (TG) and Body Mass Index (BMI). The study was carried out in the Department of Biochemistry Chittagong Medical College during the period of January 2010- December 2010. Samples were collected from population of different area of Chittagong City Corporation of different occupations, age from 35- 60 years. The data were collected by a structured questionaries which includes age, sex, occupation, dietary habits, family history of hyperlipidemia and DM. BMI was calculated by standardized protocol. Population suffering from DM, renal diseases and other endocrine disease were excluded. A total of 105 subjects were included in this study. Among them 70 were considered as case ( whose BMI was 25 kg/m2) and 35 were considered as control ( whose BMI was < 25 Kg/ m2).Serum Total cholesterol, LDL-C, HDL-C and TG were measured in all samples in fasting state. Study showed that female were more obese than male,( 31.14 +2.23kg/m2 Vs 29.71 +2.69kg/mo), p=